Novel bithienyl-benzimidazoles: one-pot synthesis and optical and solvatochromic studies - Batista, R. M. F. (2017)
Novel bithienyl-benzimidazoles were synthesised in good to excellent yields, by a one-step reaction via Na2S2O4 reduction of o-nitroaniline in the presence of formyl-bithiophenes. Using this simple and versatile method, benzimidazoles were directly obtained from several o-nitroanilines and aldehydes, via a reductive cyclization without purification of any intermediate. Evaluation of the optical and solvatochromic properties of these compounds was carried out.